1998
DOI: 10.1038/bjc.1998.151
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl transferase 1: two polymorphisms in coding sequence identified in colorectal cancer patients

Abstract: Summary Increased cancer risk has been associated with functional polymorphisms that occur within the genes coding for the Nacetyltransferase enzymes NAT1 and NAT2. We detected two NAT1 polymorphisms in colorectal cancer patients by heteroduplex analysis. DNA sequencing revealed the wild-type sequence (NAT1*4) and two single base substitutions at adjacent positions 999 bp (C to T, NAT1*14) and 1000 bp (G to A, NAT1*15) of the gene, changing Arg187 to a stop codon and Arg187 to Gin respectively. NAT1 alleles NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Inability to discriminate NAT1*10 from NAT1*14 is hardly likely to have a major effect on the outcome of the NAT1 analyses. 50,53 Contrary to our results, earlier studies showed that the NAT1*10 allele was associated with higher aromatic adducts in the urinary bladder DNA. 54 In this study, the lack of association between NAT1 polymorphism and PhIP-DNA adducts in human lymphocytes suggests the enzyme has less effect in activating PhIP in these blood cells and does not rule out that the effect of NAT1*10 may be different in target tissues, such as colon, because of the presence of different factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Inability to discriminate NAT1*10 from NAT1*14 is hardly likely to have a major effect on the outcome of the NAT1 analyses. 50,53 Contrary to our results, earlier studies showed that the NAT1*10 allele was associated with higher aromatic adducts in the urinary bladder DNA. 54 In this study, the lack of association between NAT1 polymorphism and PhIP-DNA adducts in human lymphocytes suggests the enzyme has less effect in activating PhIP in these blood cells and does not rule out that the effect of NAT1*10 may be different in target tissues, such as colon, because of the presence of different factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Sinclair and co-workers demonstrated that a third-domain truncation mutant of human NAT1 (1-204) can bind to AcCoA, but does not have any catalytic activity in acetylating arylamines [55]. This provides the basis for the NAT1*15 allele, in which a stop codon (Arg 187 Stop) results in a truncated and catalytically inactive protein [56,57].…”
Section: Eukaryotic Natsmentioning
confidence: 97%
“…A list of the main mutations that affect amino acids in human NAT1 and NAT2 are shown in Table 1 . The premature stop codons in human NAT1 are readily understood (Hubbard et al ., 1998 ; Hughes et al ., 1998 ; Payton and Sim, 1998 ).…”
Section: Nat and Pharmacogeneticsmentioning
confidence: 99%